Correlation Between Early Diagnosis of Ovarian Neoplasm and Long-Term Prognosis - Alexandru BAROS; Alina POTORAC; Natalia TURCAN; Diana Cristina SECARA; Octavian MUNTEANU; George PARIZA; Monica Mihaela CIRSTOIU (Modern Medicine)
Ovarian cancer is the seventh most commonly diagnosed cancer in women, with the highest mortality rate among female genital cancers. Due to the nonspecific symptoms and the lack of effective screening strategies, ovarian cancer is often diagnosed in an advanced stage of the disease, with a 5-year survival rate of 25%. The efforts of specialists are aimed at identifying screening methods, with the lowest possible rates of false positive or false negative results in order to diagnose the disease at an early stage, when the 5-year survival rate is 92%. In this study we analyzed the incidence of ovarian cancer in the last five years in the Bucharest University Emergency Hospital, being registered 153 cases of ovarian cancer. The aim of this paper is to analyze the correlation between the early diagnosis of ovarian cancer and the long-term prognosis.